Ethnophysics and Technology: Physics e-module integrated with local wisdom based on an Android application - Zaini, Muhammad; Kafrawi, Muhammad; Musanni, Musanni (Department of Physics Education, Universitas Mataram, 2024)
21st century learning is a collaboration of technology and science that can change students' abilities from LOTS (lower order thinking skills) to HOTS (higher order thinking skills). In its application, 21st century learning is supported by teaching resources and media based on environmental phenomena and technological developments. This research aims to determine the feasibility of the physics e-module based android application that has been developed after validation testing by media experts, material experts, and learning experts. This e-module was developed to serve as an innovation in physics learning in schools to improve high school students from LOTS to HOTS abilities. This type of research is development research by applying 4D model consisting of define, design, develop and disseminate stages. At the define stage, researchers examine and analyze phenomena in schools such as curriculum, student learning styles, teacher teaching styles, learning resources and learning media used. In the design stage, researchers design the needs of students and teachers in learning such as learning modules. In the develop stage, researchers develop products for student learning needs through expert validation from lecturers and teachers. In the disminate stage, researchers apply products that have been developed in schools. The population of this study was all class X students at SMAN 5 Mataram. Sampling in this research was carried out using a purposive sampling method. The classes chosen as research samples were classes X IPA 1 and The average score from the media validation results was 4.8 with a very valid category. The average score from the learning validation results was 4.7 in the very valid category. Based on the validation results, it was concluded that the development product in the form of an integrated physics e-module with local wisdom based on an Android application was suitable for use in schools.